The Influence of the Film “A Home for Alie” (2025) on the Formation of Moral Character in Adolescents - Prasetyo Adinugroho; Intan Tri Kusumaningtias; Restiawan Permana (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Film as a mass medium plays a crucial role as an agent of moral value socialization, especially for adolescents who are in the critical phase of identity formation. This study aims to measure the influence of the film